Pola Dan Keragaman Pendidikan Islam (Kajian Tentang Pesantren dan Ruang Lingkupnya): Pola Dan Keragaman Pendidikan Islam - Mohammad Wisnu Khumaidi (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2020)
There is an opinion that the pesantren is rooted in Islam's own tradition of Tarikat. Pesantren has a close relationship with the special education place for the Sufi people. This opinion is based on the fact that the early first century history of Islam's entry into Indonesia is much more familiar in the form of tarikat activities. This is characterized by the formation of organization groups that carry out the practices of zikr and wirid. The Chief of the Tarikat called Kyai, which required his followers to perform the Suluk. Suluk is living with fellow Tarikat members in a mosque for 40 days to perform worship under the guidance of the Order of the order. For the purposes of these Suluk, the Kyai provides special rooms for lodging and cooking places located on the left-hand of the mosque. Besides teaching the practices of the order, the followers also taught the books of religion in various branches of Islamic sciences. The activities performed by the followers of this order are then called the study. In the next development, this institution grew and developed into a pesantren. Thus, the pesantren at that time served as a center of Islamic teaching and education and the center of the spread of Islamic religion.